Главная

Алгебра 8 класс Ю.Н.Макарычев, Н.Г.Миндюк, К.И.Нешков, С.Б.Суворова

ГДЗ учебник по алгебре 8 класс Ю.Н.Макарычев, Н.Г.Миндюк, К.И.Нешков, С.Б.Суворова

авторы: , , , .
издательство: "Просвещение" 2013 г

Раздел:

Номер №231

Упростите выражение:
а)
5 y 3 + 1 y + 3 4 y 18 y 2 9
;
б)
2 a 2 a + 3 + 5 3 2 a 4 a 2 + 9 4 a 2 9
;
в)
4 m 4 m 2 1 2 m + 1 6 m 3 + 2 m 1 4 m + 2
;
г)
1 ( x + y ) 2 2 x 2 y 2 + 1 ( x y ) 2
;
д)
4 a 2 + 3 a + 2 a 3 1 1 2 a a 2 + a + 1
;
е)
x y x 2 + x y + y 2 3 x y x 3 y 3 + 1 x y
.

Решение а

5 y 3 + 1 y + 3 4 y 18 y 2 9 = 5 ( y + 3 ) + ( y 3 ) ( 4 y 18 ) ( y 3 ) ( y + 3 ) = 5 y + 15 + y 3 4 y + 18 ( y 3 ) ( y + 3 ) = 30 y 2 9

Решение б

2 a 2 a + 3 + 5 3 2 a 4 a 2 + 9 4 a 2 9 = 2 a 2 a + 3 5 2 a 3 4 a 2 + 9 ( 2 a + 3 ) ( 2 a 3 ) = 2 a ( 2 a 3 ) 5 ( 2 a + 3 ) ( 4 a 2 + 9 ) ( 2 a + 3 ) ( 2 a 3 ) = 4 a 2 6 a 10 a 15 4 a 2 9 ( 2 a + 3 ) ( 2 a 3 ) = 16 a 24 ( 2 a + 3 ) ( 2 a 3 ) = 8 ( 2 a + 3 ) ( 2 a + 3 ) ( 2 a 3 ) = 8 2 a 3 = 8 3 2 a

Решение в

4 m 4 m 2 1 2 m + 1 6 m 3 + 2 m 1 4 m + 2 = 4 m ( 2 m 1 ) ( 2 m + 1 ) 2 m + 1 3 ( 2 m 1 ) + 2 m 1 2 ( m + 1 ) = 4 m 6 2 ( 2 m + 1 ) 2 + 3 ( 2 m 1 ) 2 6 ( 2 m 1 ) ( 2 m + 1 ) = 24 m 2 ( 4 m 2 + 4 m + 1 ) + 3 ( 4 m 2 4 m + 1 ) 6 ( 2 m 1 ) ( 2 m + 1 ) = 24 m 8 m 2 8 m 2 + 12 m 2 12 m + 3 6 ( 2 m 1 ) ( 2 m + 1 ) = 4 m 2 + 4 m + 1 6 ( 2 m 1 ) ( 2 m + 1 ) = ( 2 m + 1 ) 2 6 ( 2 m 1 ) ( 2 m + 1 ) = 2 m + 1 6 ( 2 m 1 )

Решение г

1 ( x + y ) 2 2 x 2 y 2 + 1 ( x y ) 2 = ( x y ) 2 2 ( x 2 y 2 ) + ( x + y ) 2 ( x + y ) 2 ( x y ) 2 = x 2 2 x y + y 2 2 x 2 + 2 y 2 + x 2 + 2 x y + y 2 ( x + y ) 2 ( x y ) 2 = 4 y 2 ( x y ) 2

Решение д

4 a 2 + 3 a + 2 a 3 1 1 2 a a 2 + a + 1 = 4 a 2 + 3 a + 2 + ( 2 a 1 ) ( a 1 ) ( a 1 ) ( a 2 + a + 1 ) = 4 a 2 + 3 a + 2 + 2 a 2 3 a + 1 ( a 1 ) ( a 2 + a + 1 ) = 6 a 2 + 3 ( a 1 ) ( a 2 + a + 1 ) = 3 ( 2 a 2 + 1 ) a 3 1

Решение е

x y x 2 + x y + y 2 3 x y x 3 y 3 + 1 x y = ( x y ) 2 3 x y + x 2 + x y + y 2 ( x y ) ( x 2 + x y + y 2 ) = x 2 2 x y + y 2 2 x y + x 2 + y 2 ( x y ) ( x 2 + x y + y 2 ) = 2 ( x 2 2 x y + y 2 ) ( x y ) ( x 2 + x y + y 2 ) = 2 ( x y ) 2 ( x y ) ( x 2 + x y + y 2 ) = 2 ( x y ) x 2 + x y + y 2